The Rise of Emerging Donors: Exploring Motives Behind Indonesian AID’s Development Assistance to African Countries - Muhammad Faisal Javier Anwar; Ahmad Salim (Institute of International Studies, 2025)
This research examines the motivations behind Indonesia’s development assistance to African countries through Indonesian AID, highlighting Indonesia within the broader context of the rise of emerging donors in global development. A qualitative explanatory approach was employed, with data collected via semi-structured interviews with a key policymaker and library research. The data were then analyzed using the foreign policy analysis framework with a pluralist perspective, which integrates both domestic and international factors. The findings reveal that Indonesia’s aid to Africa is driven by a combination of pragmatic material interests, such as promoting economic diplomacy and expanding trade opportunities, and normative aspirations, including South-South cooperation and enhancing Indonesia’s international standing. The study under discussion highlights the intersection of several factors, including leaders’ idiosyncrasies, domestic politics, and global politics, which collectively influence the motivations behind aid. This intersection transcends the conventional binary of normative versus material drivers. By focusing on Indonesia’s involvement in Africa, this research addresses a gap in the literature on Indonesia’s developmental assistance, which has predominantly focused on Oceania, thereby illustrating the intricate interplay between domestic and international factors in the foreign aid strategies of emerging donors. The paper concludes that Indonesia’s approach reflects a nuanced donor identity, offering practical implications for understanding the evolving landscape of South-South cooperation and the diversification of global development assistance.